Competency And Character Based Integrative Assessment Model In Islamic Religious Education (PAI) Learning - Siti Khoerunnisa; Siti Atiqoh; Siti Lathifah; Akil; Abdul Azis (Penerbit Hellow Pustaka, 2025)
Assessment in Islamic Religious Education (PAI) learning is often still focused on the cognitive aspect, while the affective and psychomotor aspects receive insufficient attention. This contradicts the principle of educational assessment, which should holistically encompass knowledge, attitudes, and skills. This study aims to examine the implementation of assessment in all three aspects of PAI across various educational levels, identify challenges in developing a holistic assessment system, and propose an integrative assessment model based on competencies and character within the context of the Merdeka Curriculum. The method used is a qualitative study with a descriptive-analytic approach based on literature review and document analysis. The results show that affective and psychomotor assessments are still partial and lack standardization, especially outside Islamic educational institutions such as pesantren. The main challenges include limited assessment instruments, the absence of cross-level guidelines, and low teacher capacity in designing holistic assessments. Therefore, an integrative assessment model is needed that aligns with the principles of the Merdeka Curriculum, combining authentic and character-based assessments. This study offers an assessment framework that includes indicators of spiritual, social, cognitive, and religious practice competencies. It is expected that this model can serve as a solution in realizing a well-rounded and balanced Pancasila student profile.